2020
DOI: 10.1002/qua.26563
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study on the atmospheric degradation mechanism and subsequent products of E,E‐2,4‐hexadienal with hydroxyl radical

Abstract: E,E‐2,4‐hexadienal is probably a precursor of secondary organic aerosol (SOA) and plays an important role in the atmospheric chemistry. Its main degradation routs are the reactions with OH, Cl, NO3 as well as photolysis. Atmospheric hydroxyl radical, as the most important oxidant, generally controls the removal of volatile organic compounds in the atmosphere. Thus, the quantum chemical calculations are used to investigate the reaction mechanism of E,E‐2,4‐hexadienal with hydroxyl radical, which would give us a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Because the OH radicals control the removal of the volatile organic compounds in the atmosphere, C 3 F 4 is degraded predominantly via the reaction with OH radicals. The energetic profiles for the C 3 F 4 + OH reaction are illustrated in Figure and the detailed energetic data are available in the Supporting Information (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Because the OH radicals control the removal of the volatile organic compounds in the atmosphere, C 3 F 4 is degraded predominantly via the reaction with OH radicals. The energetic profiles for the C 3 F 4 + OH reaction are illustrated in Figure and the detailed energetic data are available in the Supporting Information (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…The Fukui function based on DFT was successfully adopted in order to predict the attacking site of the reactant molecules [ 53 , 54 , 55 ]. For the Fukui function, the following three situations were as follows: where f k + , f k − and f k 0 represent nucleophilic, electrophilic, and radical attacks, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is essential to study the subsequent reactions of this product in order to assess the risk of these products in an aquatic environment. The Fukui function based on DFT was successfully adopted in order to predict the attacking site of the reactant molecules [53][54][55]. For the Fukui function, the following three situations were as follows:…”
Section: Further Conversion Reactions Of M-pmentioning
confidence: 99%
“…Reaction of E,E-2,4-hexadienal with hydroxyl radical was also theoretically studied by Sun et al [6]. The authors concluded that E-butenedial was the dominant product of hexadienal photooxidation.…”
Section: Introductionmentioning
confidence: 98%